Unveiling The Merdeka Curriculum: A Comprehensive Inquiry Into Islamic Religious Education Transformation At Vocational High School - Hasanah, Uswatun; Apriyani, Hikma (Journal of Islamic Education Policy, 2025)
This study comprehensively investigates the transformation process of Islamic religious education in Vocational High Schools (SMK) as it adapts the Merdeka Belajar Curriculum introduced by the Indonesian Ministry of Education and Culture. The research was carried out at SMKN 2 Bandar Lampung, one of the top vocational schools in Lampung province. The primary goal of this study is to investigate the changes in planning, learning methods, learning materials, assessment, and the future of Islamic religious education in response to the adoption of the Merdeka Belajar Curriculum. This study also examines the problems, opportunities, and implications of transforming Islamic religious education in the vocational setting in response to today's more complicated needs. Data were obtained using a qualitative approach, including classroom observations, in-depth interviews with teachers, principals, and students, and document analysis. The research findings revealed that SMKN 2 Bandar Lampung employed various methods to align Islamic religious education learning with the Merdeka Belajar Curriculum principles. The methods include developing contextual teaching modules, using innovative learning approaches like project-based learning, collaborative case studies, and industry partnerships, and incorporating digital technologies into the teaching and learning process. In conclusion, this study contributes to a better understanding of the transformation efforts of Islamic religious education in vocational high schools in response to changes in the national curriculum. The study's findings can be utilized to help other vocational schools improve the quality of Islamic religious education and prepare students for the challenges of the modern workplace.